Human Fecal Microbiota Transplantation Reduces the Susceptibility to Dextran Sulfate Sodium-Induced Germ-Free Mouse Colitis - Yang, Yapeng; Zheng, Xiaojiao; Wang, Yuqing; Tan, Xiang; Zou, Huicong; Feng, Shuaifei; Zhang, Hang; Zhang, Zeyue; He, Jinhui; Cui, Bota; Zhang, Xueying; Wu, Zhifeng; et al. (Frontiers in Immunology, 2022)
In clinical practice, fecal microbiota transplantation (FMT) has been used to treat inflammatory bowel disease (IBD), and has shown certain effects. However, the selection of FMT donors and the mechanism underlying the effect of FMT intervention in IBD require further exploration. In this study, dextran sodium sulfate (DSS)-induced colitis mice were used to determine the differences in the protection of colitis symptoms, inflammation, and intestinal barrier, by FMT from two donors. Intriguingly, pre-administration of healthy bacterial fluid significantly relieved the symptoms of colitis compared to the ulcerative colitis (UC) bacteria. In addition, healthy donor (HD) bacteria significantly reduced the levels of inflammatory markers Myeloperoxidase (MPO) and Eosinophil peroxidase (EPO), and various pro-inflammatory factors, in colitis mice, and increased the secretion of the anti-inflammatory factor IL-10. Metagenomic sequencing indicated higher species diversity and higher abundance of anti-inflammatory bacteria in the HD intervention group, including Alistipes putredinis, Akkermansia muciniphila, Bifidobacterium adolescentis, short-chain fatty acids (SCFAs)-producing bacterium Christensenella minuta, and secondary bile acids (SBAs)-producing bacterium Clostridium leptum. In the UC intervention group, the SCFA-producing bacterium Bacteroides stercoris, IBD-related bacterium Ruminococcus gnavus, Enterococcus faecalis, and the conditional pathogen Bacteroides caccae, were more abundant. Metabolomics analysis showed that the two types of FMT significantly modulated the metabolism of DSS-induced mice. Moreover, compared with the UC intervention group, indoleacetic acid and unsaturated fatty acids (DHA, DPA, and EPA) with anti-inflammatory effects were significantly enriched in the HD intervention group. In summary, these results indicate that FMT can alleviate the symptoms of colitis, and the effect of HD intervention is better than that of UC intervention. This study offers new insights into the mechanisms of FMT clinical intervention in IBD.